State-of-the-art laser Doppler systems development for turbulence measurements - Mohd Rusdy Yaacob (2019)
This thesis, as stated in the title, emphasizes on the deve]opmeht of a novel, software-driven laser Doppler anemometer (LDA) system followed by the experimental investigation on the turbulence in a round jet. The former has been driven by the practical limitations suffered by the commercial LDA system, which affect the accuracy of the difficult turbulence measurement. The latter has been inspired by the unsolved and underexplored developing turbulence, which is more difficult to measure than the fully developed counterpart. The challenge is to measure high intensity and high shear turbulence. This will be further elaborated in Chapter 1. The novel LDA System comprising the state-of-the-art, off-the-shelf hardware and a novel software for signal and data processing, which will be described in detail in Chapter 2. This chapter will also demonstrate the procedures for measurements and data analysis using the software, while highlighting some challenges that arose before obtaining the desired outcomes, which are later presented in Chapter 3. Some of the outcomes have already been published in two indexed journals and a conference proceeding, while the rest have been properly documented in three completed manuscripts. The ultimate aim of this thesis is to enhance the understanding of the underlying physics of turbulence and investigate whether the existing turbulence models need be corrected. This thesis| is also intended to provide comprehensive: information and thorough guidance for anyone who is going to operate the herein described LDA system independently in the future.